IMPORTANCE OF MONITORING MATRIX METALLOPROTEINASE-3 LEVELS IN PATIENTS WITH RHEUMATOID ARTHRITIS - Iroda X. Xadjimatova ,; Ma`rif Sh. Karimov ,; Dilorom A. Abzalova , (Central Asian Journal of Medicine, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by persistent synovial inflammation and gradually progressive bone destruction. Matrix metalloproteinases (MMPs), a family of zinc-containing enzymes, have been found to play an important role in the degradation and remodeling of the extracellular matrix (ECM). Matrix metalloproteinases (MMPs) are involved in cell proliferation, migration, inflammation, and cell metabolism. More and more people are paying attention to their function in inflammatory and immune diseases.